FINANCIAL INCLUSION FOR WOMEN: BARRIERS, STRATEGIES, AND PROGRESS IN ACCESSING FINANCIAL SERVICES WITH A GENDER PERSPECTIVE - Bouroncle Velásquez, Mauricio (2025)
Financial inclusion is defined as the effective access and responsible use of financial products and services that help individuals and businesses meet basic needs and strengthen their economic well-being. This concept has gained global relevance due to its relationship with poverty reduction and the promotion of gender equality, although significant gaps persist that restrict women’s full participation. These inequalities reflect historical patterns of exclusion that hinder the social and economic development of communities. This study aimed to identify factors, strategies, technologies, and regulatory frameworks that impact women’s financial inclusion through a systematic review of recent literature. To this end, the PRISMA 2020 methodology was applied, which establishes an orderly and rigorous process to ensure transparency and robustness in the synthesis of evidence. The resulting reflection allows us to recognize that financial inclusion is a dynamic process that demands comprehensive approaches, coordination between actors, and interventions sensitive to local contexts. Consolidating sustainable progress requires revising traditional models and investing in capacities that promote women’s economic autonomy.